The Role of the Central Election Committee (CEC) of the USSR and the All-Union Migration Committee in Regulating Peasant Resettlement in Zhetysu (Semirechye) in the 20s of the XX Century - N. Miymanbaeva, Fyalka; S. Zhugenbaeva, Gulbanu; T. Kartabaeva, Erke; Zh. Oten, Gulgazira; K. Dusembekova, Zhanna; B. Dengelbayeva, Nazgul (International Journal of Psychosocial Rehabilitation, 2020)
The present research aims to study the role of the CEC USSR (as the highest authority of the USSR) and the All-Union Migration Committee of the CEC USSR in peasant resettlement in Zhetysu in the 1920s. The scientific relevance is due to the fact the aforementioned issue remains insufficiently studied. The archive materials from Russia and Kazakhstan were studied and analyzed. The leading research method is source study and comparative analysis, which allow revealing the activities of the highest state authorities in carrying out peasant resettlement in Kazakhstan. The article presents materials on peasant resettlement immediately after the October Revolution; the settlement was carried out by the USSR People’s Commissariat of Agriculture using the prerevolutionary experience of peasant colonization development. The commissariat put forward the land management of immigrants as one of the main events. It is noted that major resettlement areas were the Kazakh SSR and the Kyrgyz Autonomous Region, in particular, Zhetysu, where land and water reform was one of the first measures in this direction. Reveals Reform in Zhetysu is revealed, the order of the population settlement is indicated, and political mistakes in the reform are discussed. The state significance of resettlements in the article is emphasized by the creation (with the direct support of the state) of resettlement bodies, in particular the All-Union Settlement Committee, which were interested in the influx of labor force, as well as by the formation of a financial support system, which was the material basis and an important stimulus for the resettlement movement. Since the mid 1920s, resettlement was carried out in accordance with the plans for the national economy’s development; it was voluntary and took into account the interests of society. However, in the late 1920s it became clear that peasant resettlement exhausted its resources and did not justify the state expenses, so with time it began to decline. The materials of the present study are of practical value for disclosing the peasantry history and of new forms of management in the Soviet period.